2009
DOI: 10.1007/s12039-009-0068-x
|View full text |Cite
|
Sign up to set email alerts
|

Test of theoretical models for ultrafast heterogeneous electron transfer with femtosecond two-photon photoemission data

Abstract: Abstract. The energy distribution of electrons injected into acceptor states on the surface of TiO 2 was measured with femtosecond two-photon photoemission. Shape and relative energetic position of these distribution curves with respect to the corresponding donor states, i.e. of perylene chromophores in the first excited singlet state attached via different bridge-anchor groups to the TiO 2 surface, were compared with the predictions of different theoretical models for light-induced ultrafast heterogeneous ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 45 publications
4
32
1
Order By: Relevance
“…As a benchmark dye, we use perylenecarboxylic acid, which provides fast electron injection into TiO 2 and has been a subject of several experimental and theoretical studies of charge transfer rates. [34][35][36]39,44,45 The injection times calculated using this molecule's LUMO energy (À2.37 eV according to our DFT B3LYP calculations) as the injection energy are presented in the third column of Table 2 for all computed adsorption geometries. The injection times for the most stable configuration on each surface are plotted in Fig.…”
Section: Charge Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a benchmark dye, we use perylenecarboxylic acid, which provides fast electron injection into TiO 2 and has been a subject of several experimental and theoretical studies of charge transfer rates. [34][35][36]39,44,45 The injection times calculated using this molecule's LUMO energy (À2.37 eV according to our DFT B3LYP calculations) as the injection energy are presented in the third column of Table 2 for all computed adsorption geometries. The injection times for the most stable configuration on each surface are plotted in Fig.…”
Section: Charge Injectionmentioning
confidence: 99%
“…All of these surfaces have been observed in anatase particles used in DSSC, 1,32 (101) is the dominant surface, but there are also synthetic routes to produce (001) and (100) surfaces in large amounts. [10][11][12][13][14][15][16][17] With these surfaces, we use the same dye -perylenecarboxylic acid, which is a common model system for time-resolved experimental studies of charge injection 34,35,45 and which shows a fast injection time according to experiments 34,35,45 and calculations. 36,39,42,43 We outline our computational setup and the procedure to calculate injection times in Section 2.…”
Section: Introductionmentioning
confidence: 99%
“…35 On the basis of ultraviolet photoemission spectroscopy and twophoton photoemission, Gundlach et al reported a vibrational excited ionized perylene dye along with a broad energy distribution of electrons injected to the TiO 2 . 44,45 In contrast to these investigations, wave packets in real time at distinct probe wavelengths are measured in our study. The results allows to unambiguously trace the source of the observed vibrational modes.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Molecular model systems that are designed to satisfy the experimental requirements as well as the computational capabilities are essential for investigating new concepts in IET. Perylene-based sensitizers have proven to be well suited for ultrafast spectroscopic investigations of IET while still being accessible to combined nonadiabatic quantum mechanics/molecular mechanics (QM/MM) simulations. , …”
Section: Introductionmentioning
confidence: 99%